Isolation and identification of phytochelatin-producing fungi associated with mangroves - Noor Afiza Badaluddin (Fakulti Sains dan Teknologi, 2012)
Fungi play important roles in some of the major ecosystem processes including heavy metal detoxification. The roles of phytochelatins in heavy metal detoxification by fungi have not been widely investigated.